A comparison of some physical abilities between futsal and open football players - Ayyd Ali Adhab Al-Saedi,; Ali Shakir Obaid Al-Sultani,; Hussein Ali Hasan Al-Taie, (Eximia, 2023)
The aim of the research is to identify the differences in some of the physical abilities of football players in open stadiums and halls (futsal), as the researchers assume that there are significant differences in some of the physical abilities studied. The researchers used the descriptive approach using the comparative survey method to suit the nature of the problem of the study. The researchers reached the conclusion that there are Statistical significance for some of the physical abilities investigated and in favor of futsal players.